Brain metabolism changes in middle‐aged asymptomatic APOE‐ε4 carriers. The PESA Study. (20th December 2022) - Tristão‐Pereira, Catarina; Toribio‐Fernández, Raquel; Sanchez‐Gonzalez, Javier; Gispert, Juan Domingo; Ibañez, Borja; Cortes‐Canteli, Marta; Fuster, Valentin
Abstract: Background: Apolipoprotein E ( APOE ) is the major genetic risk factor for late‐onset Alzheimer's disease (AD) and is implicated in cardiovascular disease. The APOE ‐ε4 allele is associated with brain hypometabolism in AD, mild cognitive impairment (MCI) ( Mosconi et al. Neurology 2004 ) and in cognitively unimpaired middle‐aged individuals ( Reiman et al. NEJM 1996 ). Greater longitudinal decreases in brain metabolism were reported in APOE ‐ε4 carriers with MCI ( Paranjpe et al. Neuroimage Clin 2019 ), but studies on brain metabolism longitudinal changes in unimpaired middle‐aged APOE ‐ε4 carriers are scarce and with relatively small sample sizes ( Reiman et al. PNAS 2001 ). The Progression of Early Subclinical Atherosclerosis (PESA) study is a longitudinal study following >4000 asymptomatic middle‐aged subjects deeply screened for cardiovascular risk factors (CVRFs) ( Fernandez‐Ortiz et al. AHJ 2013 ). Individuals with the highest burden of atherosclerosis underwent FDG‐PET at baseline and CVRFs were associated with hypometabolism in AD regions (Cortés‐Canteli & Gispert et al. JACC 2021). Those individuals underwent a 6‐year follow‐up FDG‐PET. Here, we investigate the effect of APOE genotype on brain metabolism progression in middle‐aged asymptomatic individuals. Method: 365 cognitively unimpaired adults (mean age 50 years old) were genotyped for APOE and underwent two FDG‐PET studies ( Table ). Baseline and follow‐up images were spatially normalized to a group template in the MNI space. FDG‐uptake was normalized to the pons and images were subtracted, yielding a measure of brain metabolic change. An ANOVA model was carried out to compare brain metabolism change between APOE‐ Result: At the global level, we observed significantly greater decreases in FDG uptake in ε4 carriers compared to the reference ε3/ε3 genotype (p=0.024). Voxelwise analysis showed greater decreases between ε4 carriers and non‐ε4 carriers in the precuneus, supramarginal gyrus, hippocampus and anterior cingulate gyrus ( Figure ). Conclusion: Asymptomatic middle‐aged APOE ‐ε4 carriers have a greater decline in brain metabolism in regions known to display hypometabolism in AD, suggesting an increased vulnerability. Further analysis will reveal the extent to which AD pathology and/or other risk factors may mediate this association.